Daintiest dynamos [nuclear microbatteries]. - Lal, A. (IEEE spectrum)
Research groups at Cornell University and the University of Wisconsin have been working on a way to harvest the energy released naturally by tiny bits of radioactive material, specifically, the energy that comes from high-energy particles spontaneously emitted by radioactive elements. Their research involves developing devices, called nuclear microbatteries, made from thin radioactive films that pack in energy at densities thousands of times greater than those of lithium-ion batteries. Nuclear microbatteries may ultimately change the way many electronic devices are powered. The prevalent power source paradigm is to have all components in a device's circuitry drain energy from a single battery. With nuclear microbatteries, it will be possible to provide a power source for each component. Thus, even if a main battery is still necessary for more power hungry components, it could be considerably smaller and the multiple nuclear microbatteries could run a device for months or years, rather than days or hours. The future of nuclear microbatteries depends on several factors such as safety, efficiency and cost. If the amount of radioactive material in the devices is kept small, they emit so little radiation that they can be safe with only simple packaging. It is also important to find ways to increase the amount of energy that nuclear microbatteries can produce, especially as the conversion efficiency begins approaching the targeted 20 percent.